Analysis Of The Needs Of Children With Special Needs (Tunagrahita) In Physical Education Learning At Sd Level In Skh Pandeglang - Devaron Suardi; Idris Supriadi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
The purpose of this research is to analyze the needs in the learning process of children with special needs in physical education learning. The method used in this research is descriptive qualitative method using data triangulation techniques, namely the series of observations, documentation and interviews. The subjects in this study were peserda basic level points at SKh 1 Pembina Pandeglang. This research reveals the needs needed in the learning of children with special needs. These needs are 1) Synchronizing understanding of the learning objectives of physical education for the elementary school level. 2) Better understand the personality of students 3) Conduct a comprehensive approach to students 4) Modify suggestions according to the needs in the learning process while still prioritizing the level of safety for students. Systematic and structured physical education learning will have a positive impact on the basic movement skills of students in general. By improving the skills of participants or children with special needs, it has indirectly provided encouragement and confidence for children with special needs to socialize and feel recognized by the surrounding community. Systematic and structured physical education learning will have a positive impact on the basic movement skills of students in general. By improving the skills of participants or children with special needs, it indirectly gives encouragement and confidence to children with special needs to get along and feel recognized by the surrounding community. Systematic and structured physical education learning will have a positive impact on the basic movement skills of students in general. By improving the skills of participants or children with special needs, it indirectly gives encouragement and confidence to children with special needs to get along and feel recognized by the surrounding community.